Thiamine, Riboflavin and Magnesium Level Correction in Improving the Quality of Life of Patients with Chronic Heart Failure - Fatima Dzalaeva (Journal of Global Pharma Technology, 2016)
Data are presented on the effectiveness of treating patients with chronic heart failure (CHF) with vitamins B1, B2 and magnesium (Mg) added to the standard complex therapy. The group of patients with cardiovascular diseases (CVDs) consisted of 143 patients with CHF I-III functional class according to NYHA (New York Heart Association Functional Classification), as a complication of coronary heart disease (CHD). To determine the preferred doses of vitamins B1 and B2, we studied the dynamics of the concentration of thiamine (B1) and riboflavin (B2) in blood plasma and their daily excretion with a single intake of vitamins by healthy volunteers at doses of 10, 20 and 30 mg. To determine the preferred magnesium-containing drug, Mg concentration dynamics in the blood plasma of healthy volunteers were studied when taken orally in an equal dose in the form of Mg oxide and in the form of Mg orotate. The study involved 80 healthy volunteers. In order to improve the quality of life for patients with CHF and increase tolerance to physical exertion, it is advisable to add Mg in combination with vitamin B1 and B2 in the standard complex therapy. When Mg salts are added to the standard complex treatment of CHF, it is preferable to use Mg orotate. When using vitamin B1 (thiamine), it is not advised to increase the daily dose of more than 10 mg/day, since this leads to a progressive increase in the excretion of this vitamin B1 and vitamin B2.Keywords: Chronic heart failure, Therapy, Mg salts, Thiamine (B1), Riboflavin (B2).